2018
DOI: 10.1371/journal.pgen.1007260
|View full text |Cite
|
Sign up to set email alerts
|

Distinct interactions of Sox5 and Sox10 in fate specification of pigment cells in medaka and zebrafish

Abstract: Mechanisms generating diverse cell types from multipotent progenitors are fundamental for normal development. Pigment cells are derived from multipotent neural crest cells and their diversity in teleosts provides an excellent model for studying mechanisms controlling fate specification of distinct cell types. Zebrafish have three types of pigment cells (melanocytes, iridophores and xanthophores) while medaka have four (three shared with zebrafish, plus leucophores), raising questions about how conserved mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 69 publications
5
61
0
Order By: Relevance
“…This view is crystallised in the iconic Waddington landscape model of stem cell development (Waddington 1957). Consistent with this view, aside from the chromatoblast, these partially-restricted intermediates for pigment cells have been suggested to include bipotent Schwann cell precursors, capable of forming melanocytes as well as Schwann cells (Adameyko et al 2009;Adameyko and Lallemend 2010); bipotent melanoiridoblasts (Curran et al 2010), and bipotent xantholeucoblasts (Nagao et al 2014(Nagao et al , 2018.…”
Section: Introductionmentioning
confidence: 82%
“…This view is crystallised in the iconic Waddington landscape model of stem cell development (Waddington 1957). Consistent with this view, aside from the chromatoblast, these partially-restricted intermediates for pigment cells have been suggested to include bipotent Schwann cell precursors, capable of forming melanocytes as well as Schwann cells (Adameyko et al 2009;Adameyko and Lallemend 2010); bipotent melanoiridoblasts (Curran et al 2010), and bipotent xantholeucoblasts (Nagao et al 2014(Nagao et al , 2018.…”
Section: Introductionmentioning
confidence: 82%
“…However, two previous studies are of particular interest in regards to this. The study by Nagao and colleagues [ 63 ] investigated the leucophore pigment cell type in the perciform lineage. Experimental evidence suggests that the origin of the leucophore in the perciform lineage was achieved by a change in the functional interaction between TFs already expressed in a precursor cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that the same gene can be involved in the development of the same pigment cell type but in different ways in various fish species. For instance, xanthophore differentiation requires the expression of sox5 in medaka whereas the repression of this gene is required in zebrafish [60].…”
Section: Box 1 Pigmentation Genesmentioning
confidence: 99%